In vivo fluorescence imaging of exogenous enzyme activity in the gastrointestinal tract - Fuhrmann, Gregor; Leroux, Jean-Christophe (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Exogenous enzymes are administered orally to treat several diseases, such as pancreatic insufficiency and lactose intolerance. Due to the proteinaceous nature of enzymes, they are subject to inactivation and/or digestion in the gastrointestinal (GI) tract. Here we describe a convenient fluorescence-based assay to monitor the activity of therapeutic enzymes in real time in vivo in the GI tract. To establish the proof of principle, the assay was applied to proline-specific endopeptidases (PEPs), a group of enzymes recently proposed as adjuvant therapy for celiac disease (a highly prevalent immunogenetic enteropathy). A short PEP-specific peptide sequence which is part of larger immunotoxic sequences of gluten was labeled with a fluorescent dye and a corresponding quencher. Upon enzymatic cleavage, the fluorescence emission was dequenched and detected with an in vivo imaging system. PEPs originating from Flavobacterium meningosepticum (FM) and Myxococcus xanthus (MX) were evaluated after oral administration in rats. While MX PEP could not cleave the peptide in the stomach, FM PEP showed significant gastric activity reaching 40-60% of the maximal in vivo signal intensity. However, both enzymes produced comparable fluorescence signals in the small intestine. Coadministration of an antacid drug significantly enhanced MX PEP's gastric activity due to increased pH and/or inhibition of stomach proteases. With this simple procedure, differences in the in vivo performance of PEPs, which could not be identified under in vitro conditions, were detected. This imaging assay could be used to study other oral enzymes in vivo and therefore be instrumental in improving their therapeutic efficiency.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Autoimmune disease; Celiac sprue; Prolyl oligopeptidase